Arteriovenous fistulas for hemodialysis: Surgical Clinic Experience "B" - López Chapuis, Daniel; Garrido, Pedro; Elters, Antoine; Prego, Alfredo; Valverdu, Martín (Cirugía del Uruguay, 1993)
113 arterio-venous fistulas far hemodialysis performed at Clínica Quirúrgica B are analyzed. During a period of 30 months the following arterio-venous fistulas were made: 65 radial ones (general/y as a first vascular access), 30 humero axilary ones (2 with saphena and the rest with prosthesis) and 18 humero-cephalic ones. A high percentage of initial success is obtained; 87% of the angioaccesses could be used far hemodialysis.